2017
DOI: 10.1051/0004-6361/201731028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between turbulence energy and density variance in the solar neighbourhood molecular clouds

Abstract: The relationship between turbulence energy and gas density variance is a fundamental prediction for turbulence-dominated media and is commonly used in analytic models of star formation. We determine this relationship for 15 molecular clouds in the solar neighbourhood. We use the line widths of the CO molecule as the probe of the turbulence energy (sonic Mach number, M s ) and threedimensional models to reconstruct the density probability distribution function (ρ-PDF) of the clouds, derived using near-infrared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…The PDF widths derived in(Kainulainen & Federrath 2017) are overestimated in the context of the model presented here since they fit a single lognormal PDF rather than a lognormal + powerlaw PDF.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The PDF widths derived in(Kainulainen & Federrath 2017) are overestimated in the context of the model presented here since they fit a single lognormal PDF rather than a lognormal + powerlaw PDF.…”
mentioning
confidence: 81%
“…When the dense self-gravitating gas is in the power-law the observed gas fraction is slightly anti-correlated with sonic Mach number. This is because s t moves towards Kainulainen et al (2014) and Kainulainen & Federrath (2017). Kainulainen et al (2014) reported values of the radial density distribution slope (κ), which can be related to the power law slope as α = 3/κ.…”
Section: Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…An important distinction between the analytic SFR model derived in this work and the works of Krumholz & McKee (2005), Padoan & Nordlund (2011) and Hennebelle & Chabrier (2011) is that they provide a constant SF R f f and/or f f for given turbulence parameters, such as the sonic Mach number and the forcing, which set the lognormal width. However, it is not likely that differences in f f observed in the data is due the properties of turbulence, as most of these clouds have similar sonic Mach numbers and similar line width size relations (Kainulainen & Federrath 2017). The LN+PL model SF R f f calculation presented here is inherently time varying as the slope of the power law varies with cloud evolution due to gravitational collapse and feedback.…”
Section: Local Giant Molecular Clouds and The Starmentioning
confidence: 96%
“…These values indicate that the filament G350.5 as a whole is supersonic with a mach number of M3D > 2 (see Fig. 4b), where the 3D Mach number is M3D = √ 3σNT,int/σ th given the 1D measurement σNT,int, and assuming isotropic turbulence in three dimensions (e.g., Kainulainen & Federrath 2017).…”
Section: Velocity Dispersion Along the Filament Measured From Both 13mentioning
confidence: 96%